Isolation and pathogenicity of the novel porcine reproductive and respiratory syndrome virus 1 strain ZJ01 in South China - Ren, Bohua; Liu, Ruying; Huang, Feibao; Wu, Yu; Gao, Xiaopeng; Zhao, Haishen; Lin, Limiao; Li, Qunhui; Zhang, Xiangbin (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionThe emergence and widespread dissemination of novel Porcine Reproductive and Respiratory Syndrome Virus type 1 (PRRSV-1) strains in China pose significant challenges, leading to substantial clinical infections within swine populations. MethodsIn this study, we isolated a novel PRRSV-1 strain, designated ZJ01.ResultsWhole-genome sequencing revealed a genome length of 15,125 bp. Comprehensive phylogenetic analysis based on the complete genome sequence classified ZJ01 within a distinct new sublineage. Intriguingly, phylogenetic analysis of the ORF5 gene indicated that ZJ01 clusters with classical BJEU06-1-like strains. Molecular characterization identified unique deletions within the hypervariable regions of structural proteins: a three-amino acid deletion at positions 243-248 in GP3 and a four-amino acid deletion at positions 63-68 in GP4. Pathogenicity studies in piglets demonstrated that ZJ01 infection induces characteristic clinical signs, including pyrexia and sustained viral shedding. Post-mortem examination revealed significant lung pathology characterized by hemorrhages and lesions typical of PRRSV infection. Notably, while causing significant morbidity, the ZJ01 strain did not result in direct mortality in the infected piglets under the conditions of this study. DiscussionCollectively, this study provides a detailed characterization and pathogenic evaluation of the novel PRRSV-1 strain ZJ01, contributing essential information for the development of effective prevention and control strategies in swine farms.